Prevalence of Internet use amongst an elective spinal surgery outpatient population - Baker, Joseph F. (Springer-Verlag, 2010)
Nationally 62% of individuals in Ireland have internet access. Previous published work has suggested that internet use is higher among those with low back pain. We aimed to determine the levels of internet access and use amongst an elective spinal outpatient population and determine what characteristics influence these. We distributed a self-designed questionnaire to patients attending elective spinal outpatient clinics. Data including demographics, history of surgery, number of visits, level of satisfaction with previous consultations, access to the internet, possession of health insurance, and details regarding use of the internet to research one’s spinal complaint were collected. 213 patients completed the questionnaire. 159 (75%) had access to the internet. Of this group 48 (23%) used the internet to research their spinal condition. Increasing age, higher education level, and possession of health insurance were all significantly associated with access to the internet (p < 0.05). A higher education level predicted greater internet use while possession of insurance weakly predicted non-use (p < 0.05). In our practice, internet access is consistent with national statistics and use is comparable to previous reports. Approximately, one quarter of outpatients will use the internet to research their spinal condition. Should we use this medium to disseminate information we need to be aware some groups may not have access.